Recent Eruptions Between 2012 and 2018 Discovered at West Mata Submarine Volcano (NE Lau Basin, SW Pacific) and Characterized by New Ship, AUV, and ROV Data - Chadwick, William W.; Rubin, Kenna Harmony; Merle, Susan G.; Bobbitt, Andra M.; Kwasnitschka, Tom; Embley, Robert W. (Frontiers in Marine Science, 2019)
West Mata is a submarine volcano located in the SW Pacific Ocean between Fiji and Samoa in the NE Lau Basin. West Mata was discovered to be actively erupting at its summit in September 2008 and May 2009. Water-column chemistry and hydrophone data suggest it was probably continuously active until early 2011. Subsequent repeated bathymetric surveys of West Mata have shown that it changed to a style of frequent but intermittent eruptions away from the summit since then. We present new data from ship-based bathymetric surveys, high-resolution bathymetry from an autonomous underwater vehicle, and observations from remotely operated vehicle dives that document four additional eruptions between 2012-2018. Three of those eruptions occurred between September 2012 and March 2016; one near the summit on the upper ENE rift, a second on the NE flank away from any rift zone, and a third at the NE base of the volcano. The latter intruded a sill into a basin with thick sediments, uplifted them, and then extruded lava onto the seafloor around them. The most recent of the four eruptions occurred between March 2016 and November 2017 along the middle ENE rift zone and produced pillow lava flows with a shingled morphology and tephra as well as clastic debris that mantled the SE slope. ROV dive observations show that the shallower recent eruptions at West Mata include a substantial pyroclastic component, based on thick (>1m) tephra deposits near eruptive vents. The deepest eruption sites lack these near-vent tephra deposits, suggesting that pyroclastic activity is minimal below ~2500 mbsl. The multibeam sonar re-surveys constrain the timing, thickness, area, morphology, and volume of the new eruptions. The cumulative erupted volume since 1996 suggests that eruptions at West Mata are volume-predictable with an average eruption rate of 7.8 x 106 m3/yr. This relatively low magma supply rate and the high frequency of eruptions (every 1-2 years) suggests that the magma reservoir at West Mata is relatively small. With its frequent activity, West Mata continues to be an ideal natural laboratory for the study of submarine volcanic eruptions.